Prevalence and treatment outcomes of latent tuberculosis infection among older patients with chronic obstructive pulmonary disease in an area with intermediate tuberculosis burden - Hung-Ling Huang; Meng-Hsuan Cheng; Meng-Rui Lee; Jung-Yien Chien; Po-Liang Lu; Chau-Chyun Sheu; Jann-Yuan Wang; Inn-Wen Chong; Jinn-Moon Yang; Wei-Chang Huang (Emerging Microbes and Infections)
Chronic obstructive pulmonary disease (COPD) and aging both increase the risk of tuberculosis (TB), an important infectious disease in human. Exploring the burden and predictors of latent tuberculosis infection (LTBI) and treatment outcomes for older individuals with COPD is essential to guide LTBI intervention policy. We enrolled patients aged over 60 years with COPD between January 2021 and June 2023 for LTBI screening using interferon-gamma release assay (IGRA). LTBI treatment options included all World Health Organization (WHO)-recommended regimens. The final regimen was selected through shared decision-making between patients and their COPD physicians, leveraging the long-standing rapport being established. We investigated the prevalence of LTBI in this population, identified risk factors using logistic regression analysis, and evaluated treatment outcomes. A total of 810 COPD patients (mean: 72.8-years) underwent LTBI screening, with an IGRA-positive rate of 23.8%. IGRA positivity was correlated with smoking pack-years (adjusted odds ratio [aOR]: 1.02, p < 0.001), current smoking status (aOR 1.40, p = 0.030), COPD duration (aOR 1.10, p = 0.03), inhaled corticosteroid use (aOR 3.06, p < 0.001), and a cumulative equivalent dose of prednisolone exceeding 210 mg over 2 years (aOR 3.13, p < 0.001). Treatment was initiated in 150 patients (77.7%), predominantly with weekly rifapentine plus isoniazid (3HP) (60.7%). The overall completion rate was 82.0%, with adverse reactions being the primary reason for discontinuation. Our findings support that the LTBI intervention is recommended for older patients with COPD, especially those at higher risk, as nearly 25% of them have tuberculosis infection. The high treatment completion rate highlights the safety and feasibility of the WHO-recommended regimens.